PRINSIP-PRINSIP PERKAWINAN (Analisis Filosofis Implementasi dalam Meminimalisir Angka Perceraian) - Mohamad Rana; Usep Saepullah (Mahkamah : Jurnal Kajian Hukum Islam, 2021)
Marriage is a sunnatullāh that applies to His creatures, including humans. However, Allah Most High, outlined rules for humans to vent their sexual desires for a sense of tranquility (sakīnah) and pour out love and affection for their partners through the institution of marriage that He has established. In the formation of a family, Islam itself outlines the nature of marriage which it expresses as an effort to realize sakīnah, mawaddah, and raḥmah. There are such principles contained in an-nusḥuṣ al-muqaddasah as human guidance to create and realize the family order as outlined in the Koran.